DNA Barcoding dan Filogeni Molekukuler Belangkas Tachypleus (Horseshoe crab) dari Pulau Madura, Jawa Timur, Indonesia - Rafsanjani, Deni; Nugraha, Wahyu Andy; Insafitri, Insafitri (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Horseshoe crab is a marine animal that is often found in Madura waters. Horseshoe crab is Indonesia's marine biodiversity that has not been widely exploited. This aquatic animal is also called a living fossil, which means it has been alive since ancient times. Information regarding the genetic and phylogenetic structure of Horseshoe crab in the Madura area is still rarely known. Therefore, it is necessary to study to reveal the type of Horseshoe crab using the DNA barcoding method and molecular phylogeny. This research uses COI as a molecular marker, using the PCR method. With DNA barcoding, it only requires very few/small specimens but is able to document the diversity of taxonomic groups that are not yet known or come from areas that have never been identified, and is able to reveal new variations/new diversity in species that were previously classified as only one species. The results showed that the Tachypleus samples were 100% close to Tachypleus gigas. The phylogenetic results of samples from the island of Madura are in the same group as Tachypleus gigas from other locations.